1985
DOI: 10.1111/j.2042-7158.1985.tb05051.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-ionic surfactant vesicle (niosome) entrapment on the absorption and distribution of methotrexate in mice

Abstract: Non-ionic surfactant vesicles (niosomes) prepared from a non-ionic surfactant, cholesterol and dicetyl phosphate and containing methotrexate (MTX) have been administered to mice. Given intravenously the niosomes prolong the levels of MTX in the blood, large amounts of the drug being taken up by the liver. There was also an increased uptake of MTX into the brain, perhaps due to an effect of the niosome components on the permeability of the blood brain barrier. Absorption of the drug from the gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(138 citation statements)
references
References 16 publications
1
130
1
1
Order By: Relevance
“…Particle size analysis of the freshly prepared niosomes shows that the average size is~0.95 μm and the most probable size is 0.8 μm (Figure 2). Azmin et al 12 assumed that the presence of dicetylphosphate in the formulation might be responsible for producing niosomes with diameter greater than 100 nm. The use of high cholesterol content in the formulation of acyclovir niosomes may lead to large vesicle size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size analysis of the freshly prepared niosomes shows that the average size is~0.95 μm and the most probable size is 0.8 μm (Figure 2). Azmin et al 12 assumed that the presence of dicetylphosphate in the formulation might be responsible for producing niosomes with diameter greater than 100 nm. The use of high cholesterol content in the formulation of acyclovir niosomes may lead to large vesicle size.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies indicate that niosomes may increase the absorption of certain drugs from the gastrointestinal tract following oral ingestion. 12 In the present study, acyclovir-loaded niosomes were formulated and evaluated for their in vitro as well as in vivo characteristics in an attempt to improve the oral bioavailability of the drug. The in vivo evaluation of acyclovir niosomes in comparison with free drug solution was conducted in rabbits after a single oral dose.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies indicated that niosomes could prolong the plasma circulation of an entrapped drug and alter its distribution pattern and its metabolic stability [17]. Also, niosomal systems could prolong the contact time of a drug with the applied membranes in case of topical and transdermal applications [18]. Niosomes have many advantages over liposomes such as the lower cost, the greater chemical stability, and the ease of preparation and storage.…”
Section: Liposomes/niosomes and Their Pro-formsmentioning
confidence: 99%
“…Amongst various carriers utilized for target-oriented drug delivery, vesicular drug delivery systems in the form of liposome and niosomes have been most extensively investigated. Liposomal formulations have the limitation of poor stability and low drug entrapment efficiency while niosomes exhibit physical instability, aggregation, fusion, and leakage of entrapped drug, thus limiting the shelf-life of the dispersion [4,5]. Proniosomes [6] circumvent all the inherent drawbacks of niosomes and they offer a versatile vesicle delivery concept with the potential for targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%